Interaction of dopamine, female pheromones, locomotion and sex behavior in Drosophila melanogaster. - Wicker-Thomas, C.; Hamann, M. (Journal of Insect Physiology, 2008)
The regulation of female hydrocarbons and courtship behavior by dopamine and their relationship with locomotion, were investigated in Drosophila melanogaster. Ddc mutants and wild-type female flies treated with tyrosine hydroxylase inhibitors (alpha-methyltyrosine or 3-iodotyrosine) had fewer diene hydrocarbons (female pheromones) and there was a total (Ddc), partial (alpha-methyltyrosine) or no (3-iodotyrosine) rescue of hydrocarbon pattern after dopamine ingestion. There was a correlation between female pheromone level and male courtship intensity for these dopamine-depleted or rescued flies. Female locomotion was decreased in flies treated with tyrosine hydroxylase inhibitors and restored by dopamine, showing that decreased mobility of the female has little importance on male courtship. However, male courtship was inhibited by an increased mobility of dopamine-supplemented females. Tanning, which is altered in dopamine-deficient flies and in tan and ebony mutants, seemed to have no significant influence on female pheromones. Females with increased quantities of dopamine (by ingestion) exhibited larger quantities of pheromones. However, Catsup mutants did not, probably as a result of defects in the epidermis. The Dat mutation, which resulted in more dopamine being produced in the brain, showed no pheromone modification. Together, these data show a complex interaction between dopamine, female hydrocarbons, locomotion and male courtship behavior.